Development of two populations of wild banana (musa acuminata subsp. malaccensis and musa gracilis) from embryo culture technique - Unetha Balachandran (2014)
Musa acuminata and Musa gracilis are two wild bananas species that are native in Malaysia. The present study is conducted to develop clonal seed progenies from two different species of wild type bananas that is Musa acuminata subsp malaccensis and Musa gracilis from the embryo culture techniques. This study was carried out in order to study the establishment of two different species of wild banana population and determine the relationship between the rate of germination with the days of conducting embryo culture after the fruits were harvested. Three populations were established for Musa acuminata while only one population for Musa gracilis due to sample availability during sampling. Results obtained shown that there are significant difference between the days of performing embryo culture and the germination rate. The number of adequate subculture needed for producing adequate number of individual for further research is at least three subcultures with 548 initial cultures for M. gracilis. However, the number of subculture needed for Musa acuminata is not available due to time constrains. In future, further research has to be done to justify these findings. The results obtained can be used for further research in banana screening towards abiotic and biotic stress.